Meningkatkan Minat Baca Siswa-Siswi Sekolah Dasar di Jepangpakis Melalui Program Kerja Literasi Bersama UNNES GIAT 9 - Naufal, Fazrin Sulthan; Setiawan, Avi Budi; Dhini, Ania Rahma; Mustikasari, Dyah Pramesti; Ikrima, Naili (Nawadeepa: Jurnal Pengabdian Masyarakat, 2024)
This study aims to enhance reading interest and literacy among elementary school students in Jepang Pakis Village through a literacy program initiated by UNNES GIAT 9. Reading activities play a vital role in expanding knowledge and understanding. By fostering a habit of reading, students can develop their cognitive and communication skills. The research utilized a development study method with a qualitative approach. Data collection was conducted through weekly literacy sessions involving interactive reading and storytelling activities. The results demonstrate that students developed a greater enthusiasm for reading and improved their ability to retell stories they had read. Furthermore, the program significantly contributed to building students’ confidence to speak in public. This activity not only raised awareness of the importance of literacy from an early age but also equipped teachers with strategies to support students struggling with reading comprehension. The program successfully engaged students and promoted a culture of reading in the community. It is recommended that similar literacy programs be sustained and further developed to instill lifelong reading habits. Teachers and parents should continue to play a collaborative role in encouraging literacy, ensuring the continuous growth of students' intellectual and social development.